Geostatistical Mapping of Salinity Conditioned on Borehole Logs, Montebello Oil Field, California. Issue 2 (16th December 2021) - Terry, Neil; Day‐Lewis, Frederick; Landon, Matthew K.; Land, Michael; Stanton, Jennifer; Lane, John W.
Abstract: We present a geostatistics‐based stochastic salinity estimation framework for the Montebello Oil Field that capitalizes on available total dissolved solids (TDS) data from groundwater samples as well as electrical resistivity (ER) data from borehole logging. Data from TDS samples ( n  = 4924) was coded into an indicator framework based on falling below four selected thresholds (500, 1000, 3000, and 10, 000 mg/L). Collocated TDS‐ER data from the surrounding groundwater basin were then employed to produce a kernel density estimator to establish conditional probabilities for ER data ( n  = 8 boreholes) falling below the selected TDS thresholds within the Montebello Oil Field area. Directional variograms were estimated from these indicator coded data, and 500 TDS realizations from conditional indicator simulation were generated for the subsurface region above the Montebello Oil Field reservoir. Simulations were summarized as 3D maps of median TDS, most likely salinity class, and probability for exceeding each of the specified TDS thresholds. Results suggested TDS was below 500 mg/L in most of the study area, with a trend toward higher values (500 to 1000 mg/L) to the southwest; consistent with the average regional groundwater flow direction. Discrete localized zones of TDS greater than 1000 mg/L were observed, with one of these zones in the greater than 10, 000 mg/L range; however, these areas were not prevalent. The probabilistic approach used here is adaptable and is readily modified to include additional data and types and can be employed in time‐lapse salinity modeling through Bayesian updating. Abstract : Article impact statement : A three‐dimensional adaptable geostatistical approach classifying groundwater salinity above the Montebello oil field is developed and applied.